If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -1 = 2x + 35 Reorder the terms: -1 + 10x = 2x + 35 Reorder the terms: -1 + 10x = 35 + 2x Solving -1 + 10x = 35 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -1 + 10x + -2x = 35 + 2x + -2x Combine like terms: 10x + -2x = 8x -1 + 8x = 35 + 2x + -2x Combine like terms: 2x + -2x = 0 -1 + 8x = 35 + 0 -1 + 8x = 35 Add '1' to each side of the equation. -1 + 1 + 8x = 35 + 1 Combine like terms: -1 + 1 = 0 0 + 8x = 35 + 1 8x = 35 + 1 Combine like terms: 35 + 1 = 36 8x = 36 Divide each side by '8'. x = 4.5 Simplifying x = 4.5
| 3(-2m-3)=-6(5+m)+7m | | y-16=3x-15 | | 4-3y=2(2y+5)+6 | | 18and+13-5n= | | 0.12(24)+0.02x=0.06(24+x) | | 2.25t+5+13.5t=14 | | 20-2a=2(4+5a) | | 3*-.6= | | 5.4q-4.3-7.2q=-2.7-1.8q-1.6 | | 2(m-6)=4+3(3m-7) | | -4.52=3.2+1.48 | | y-2=-.5x-2 | | 2m-6(m+3)=-10 | | y=4/8 | | -0.666666667x+0.428571429=0.5 | | 39-5p=4p-8(1+7p) | | 2x+3+2x+3+3x+3x= | | -4x+2*0=-12 | | y-11=-2.5x-8 | | 93=9(k) | | y-11=-2.5x-16 | | 9x-27+1=18 | | 2m-3(m-5)=8 | | (16-8)+5= | | 36+19b=24+6 | | 38+6x=-4(7-7x) | | 4x+3+28=4x+48 | | 36-5=4 | | -7=3n+3-1 | | expression | | 15-5x=4x+18 | | 5X-3-3X+7= |